MENGEMBANGKAN AKTIVITAS DAN MOTORIK HALUS MENGGUNAKAN MODEL PROJECT BASED LEARNING, DIRECT INSTRUCTION DAN MEDIA PLAYDOUGH - Fitria, Nava Vathul; Maimunah, Maimunah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT The problem in this research focuses on the lack of learning activities and children's imitation skills, which are caused by the learning method which is still one-way (teacher-centered) and the lack of activities that can stimulate children's fine motor skills. This research takes a position as an alternative solution to this problem by implementing the Project Based Learning type and Direct Instruction as well as the use of playdough media to improve imitation skills. The research utilizes qualitative steps with the type of Classroom Action Research (CAR) which was carried out during 4 meetings in group B of Aisyiyah Bustanul Athfal 1 Banjarmasin Kindergarten with a total of 11 students. Data collection techniques include observation of teacher activities, children's activities, and assessment of imitation skills, with analytical descriptive data analysis and cross tabulation through the presentation of tables, graphs, and percentage interpretation. Research findings show that teacher activities have increased from